Access routes for infiltration of viscosuplementation in the knees of patients with grade II-III gonartrosis: Vías de acceso para la infiltración de viscosuplementación en rodillas de pacientes con gonartrosis grado II-III - Sánchez-Durán, Miguel Ángel (2021)
Introduction: Knee joint injection is a daily procedure in orthopedic outpatient visit. In order to obtain the maximum therapeutic benefit, it is necessary to perform the injection directly into the articular space and not into the adjacent structures. Objective: To establish the accuracy of the injection site into the knee joint in patients with grade II-III gonarthrosis. The portal approaches taken into consideration in this study were: Anterolateral (AL), Anteromedial (AM), Lateral Suprapatellar (LSP), Lateral mid-patellar (LMP), Medial mid-patellar (MMP) and Transtendinous (TT). Material and methods: A cross-sectional and descriptive study was conducted. A total of 123 knee joints were injected under fluoroscopy through the different approach portals. Variables: gender, positive arthrography at the first attempt, level of pain in patients during the procedure, as well as complications and side effects. Results: Lateral mid-patellar (LMP) approach was used on 20 knee joints with a 40% positive arthrography, 17 through LSP with 70.5%, 20 MMP with 90%, 21 AL with 61.3%, 26 M with 69.9%, 19 TT with 78.9%. Conclusion: The medial mid-patellar approach portal provides the greatest effectiveness in comparison to the other portals used on this study. Additionally, a greater percentage of positive arthrography was achieved at the first attempt.